Strategi Baru Guru Bimbingan Konseling dalam Pembenahan Sikap dan Disiplin Siswa SMP - Yohana Fransisca; Ely Armayani; Citra Dewi Utami; Yulia Sri Hikmah; Fakhira Batubara; Rizki akmalia (Departement of Mathematics Education, 2023)
The educational process requires discipline to develop each student's strong personality and to keep the learning and teaching environment in good condition. To establish order and discipline in schools, it is very important. Schools have an important role in determining how students behave. Student learning achievement is influenced by the level of student discipline. The purpose of this study is to analyse the new strategy of counselling guidance teachers in revamping the attitude and discipline of junior high school students. This research method is descriptive qualitative. In this research, primary data is obtained by means of interview method. The result of this research is that the involvement of school enforcers must exist in helping counselling teachers carry out their mission and duties. It will not be possible for counseling teachers to walk alone if there is a lack of support from several important parties in the school. BK teachers when carrying out their duties will be successful if BK teachers explore psychology as a provision for understanding every change in student behaviour, because if in theory BK teachers must carry out all aspects of BK but in reality in the field it will not be possible or less than optimal to apply. So the essence of BK activities, BK teachers cannot overly follow all the points of necessity when conducting guidance and counselling, because the development of the times the attitudes and characters of children have changed and of course if applied like that it will actually make the problem grow instead of being resolved.